College Algebra 7th Edition

Published by Brooks Cole
ISBN 10: 1305115546
ISBN 13: 978-1-30511-554-5

Chapter 2, Functions - Section 2.8 - One-to-One Functions and their Inverses - 2.8 Exercises: 69

Answer

$ f^{-1}(x) = (x - 2)^{3}$

Work Step by Step

$f(x) = 2 + \sqrt[3] x$ $y= 2 + \sqrt[3] x$ $y - 2 = \sqrt[3] x$ $(y - 2)^{3} = (\sqrt[3]x)^{3}$ $(y - 2)^{3} = x$ $(x - 2)^{3} = f^{-1}(x)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.